A Needs Analysis of Interactive Multimedia Based Learning Model of Single-Handed Style - Lanos, Muhsana El Cintami; Lestari, Hikmah (Universitas Negeri Semarang, 2019)
The purpose of this study was to know the needs analysis of interactive-multimedia based learning model of single-handed style. This study is in Junior High School. This study used a descriptive qualitative method. The process of collecting data used observation, interview, questionnaires, and documentation. The results of learning analysis can be described as follows: (a) the lack of student interest in learning single-handed moves due to the lack of initial knowledge about the single-handed style and at the beginning of learning the teacher only gives warming instructions. (b) In the core learning of the single-handed style, the students perform the movements exemplified by the teacher. (c) Evaluation / feedback has not been found when the learning process takes place related to the mistakes made by student movements. (d) At the end of the learning activities, students are only cool down without a thorough evaluation of the learning that has been done such as a description of the errors of movement. Theyare often done by students. (e) The absence of further explanation of the material that will be delivered by the teacher so that makes students confused when making movements at the next meeting. It can know from the percentage of students’ interesting, enthusiasm, and their agree of interactive multimedia learning. Besides that, the facilities of learning is most dominant using technology